Membaca Poststrukturalisme pada Karya Sastra - Irmayanti M. Budianto (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2007)
This paper underlines the importance of understanding post structuralism, especially the deconstructive method, in analyzing and researching literary works. There are three elements in the deconstructive method: writing, metalanguage, and the subject, which should function as analytical tools in understanding a literary work.